MgCHA particles dispersion in porous PCL scaffolds: in vitro mineralization and in vivo bone formation. (22nd June 2012) - Guarino, Vincenzo; Scaglione, Silvia; Sandri, Monica; Alvarez‐Perez, Marco A.; Tampieri, Anna; Quarto, Rodolfo; Ambrosio, Luigi
Abstract In this work, we focus on the in vitro and in vivo response of composite scaffolds obtained by incorporating Mg, CO3‐doped hydroxyapatite (HA) particles in poly(ε‐caprolactone) (PCL) porous matrices. After a complete analysis of chemical and physical properties of synthesized particles (i.e. SEM/EDS, DSC, XRD and FTIR), we demonstrate that the Mg, CO3 doping influences the surface wettability with implications upon cell–material interaction and new bone formation mechanisms. In particular, ion substitution in apatite crystals positively influences the early in vitro cellular response of human mesenchymal stem cells (hMSCs), i.e. adhesion and proliferation, and promotes an extensive mineralization of the scaffold in osteogenic medium, thus conforming to a more faithful reproduction of the native bone environment than undoped HA particles, used as control in PCL matrices. Furthermore, we demonstrate that Mg, CO3‐doped HA in PCL scaffolds support the in vivo cellular response by inducing neo‐bone formation as early as 2 months post‐implantation, and abundant mature bone tissue at the sixth month, with a lamellar structure and completely formed bone marrow. Together, these results indicate that Mg2+ and CO32– ion substitution in HA particles enhances the scaffold properties, providing the right chemical signals to combine with morphological requirements (i.e. pore size, shape and interconnectivity) to drive osteogenic response in scaffold‐aided bone regeneration. Copyright © 2012 John Wiley & Sons, Ltd.